Risk of recurrence of preexisting ocular toxoplasmosis during pregnancy - Reich, Michael; Ruppenstein, Mira Katharina; Becker, Matthias D.; Mackensen, Friederike (Ocular immunology and inflammation, 2015)
Purpose: Comparison between the risk of recurrence during pregnancy with nonpregnant periods in patients with ocular toxoplasmosis (OT).Methods: Records of 40 women were retrospectively reviewed. The women were subdivided into either a pregnant group or a control group formed by nonpregnant women during follow-up. Comparable cases from the literature were added. Mean number of recurrences per year was compared.Results: Eleven women with pregnancies could be included. Six cases from the literature were added (total n = 17). Mean number of recurrences per year during versus not during pregnancy was 0.16 (SD 0.39) versus 0.32 (SD 0.30; p = 0.088), respectively. In the control group (n = 29) the mean number of recurrences per year (0.31; SD 0.27) was significantly higher when compared to cases during pregnant periods (p = 0.002).Conclusion: Adding to published series, the presented data do not provide evidence for a relevant impact of pregnancy on recurrence behavior in OT.